Physical Quality of Cow's Milk by Exposure to Magnetic Fields Extremely Low Frequency (ELF) 300 μT and 500 μT by inhibiting Salmonella and Escherichia Coli Growth - Sudarti, Sudarti; Permatasari, Elok; Ratnasari, Indri; Laili, Sherly Nur (Indonesian Review of Physics, 2022)
Extremely Low Frequency (ELF) magnetic field, high intensity (more than 100 µT), can suppress the growth of pathogenic bacteria, but the impact of low intensity (≤ 500 µT) needs to be proven. This study aimed to analyze the physical resistance of cow's milk exposed to a magnetic field of 300 µT and 500 µT ELF by inhibiting the proliferation of Salmonella and Escherichia Coli bacteria. Completely Randomized Design (CRD) research design. Samples were 210 bottles of cow's milk (@ 50 ml) divided into seven groups. Exposure to the ELF magnetic field intensity of 300 μT and 500 μT with exposure variations of 60, 90, and 120 minutes. Result: Exposure to an ELF magnetic field with an intensity of 500 µT for 60 minutes significantly (p < 0.05) reduced the Salmonella sp. population but not Escherichia coli. Even though the physical condition showed the color and smell of fresh milk, lumps did not appear until the 10th hour. Conclusion: exposure to the ELF magnetic field intensity of 300 μT and 500 μT has not been able to maintain the quality of cow's milk.